Protocol adaptations to conduct Systematic Literature Reviews in Software Engineering: a chronological study (2015)
Systematic literature reviews (SLR) have reached a considerable level of adoption in Software Engineering (SE), how-ever protocol adaptations for its implementation remain tangentially addressed. This work provides a chronological framework for the use and adaptation of the SLR protocol, including its current status. A systematic literature search was performed, reviewing a set of twelve articles being selected in accordance with the inclusion and exclusion criteria between 2004 and 2013, using digital data sources recognized by the SE community. A chronological framework is provided that includes the current state of the protocol adaptations to conduct SLR in SE. The results indicate areas where the quantity and quality of investigations needs to be increased and the identi- fication of the main proposals providing adaptations for the protocol conducting SLR in SE.